Fundamental data for modeling electron-induced processes in plasma remediation of perfluoroalkyl substances - Sapunar, Marin; Meyer, Mackenzie; Ambalampitiya, Harindranath B; Kushner, Mark J; Mašín, Zdeněk (Physical chemistry chemical physics, 2024)
Plasma treatment of per- and polyfluoroalkyl substances (PFAS) contaminated water is a potentially energy efficient remediation method. In this treatment, an atmospheric pressure plasma interacts with surface-resident PFAS molecules. Developing a reaction mechanism and modeling of plasma-PFAS interactions requires fundamental data for electron-molecule reactions. In this paper, we present results of electron scattering calculations, potential energy landscapes and their implications for plasma modelling of a dielectric barrier discharge in PFAS contaminated gases, a first step towards modelling of plasma-water-PFAS intereactions. It is found that the plasma degradation of PFAS is dominated by dissociative electron attachment with the importance of other contributing processes varying depending on the molecule. All molecules posses a large number of shape resonances - transient negative ion states - from near-threshold up to ionization threshold. These states lie in the region of the most probable electron energies in the plasma (4-5 eV) and consequently are expected to further enhance the fragmentation dynamics in both dissociative attachment and dissociative excitation.